2005
DOI: 10.1128/jcm.43.7.3356-3363.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Panton-Valentine Leucocidin (PVL)-Positive Community-Acquired Methicillin-Resistant Staphylococcus aureus (MRSA) Strain, Another Such Strain Carrying a Multiple-Drug Resistance Plasmid, and Other More-Typical PVL-Negative MRSA Strains Found in Japan

Abstract: Community-acquired methicillin-resistant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
153
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 44 publications
7
153
1
2
Order By: Relevance
“…The results suggest that the C-MRSA strains isolated from patients with impetigo and SSSS have evolved not only ␤-lactam resistance but also multidrug resistance. Recently, skin and soft tissue infections and severe necrotizing pneumonia caused by C-MRSA strains carrying the Panton-Valentine leukocidin gene (pvl) have become a serious problem (6,21,44,51). Although screening for pvl was carried out by PCR, no pvl was detected among the C-MRSA strains used in this study (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…The results suggest that the C-MRSA strains isolated from patients with impetigo and SSSS have evolved not only ␤-lactam resistance but also multidrug resistance. Recently, skin and soft tissue infections and severe necrotizing pneumonia caused by C-MRSA strains carrying the Panton-Valentine leukocidin gene (pvl) have become a serious problem (6,21,44,51). Although screening for pvl was carried out by PCR, no pvl was detected among the C-MRSA strains used in this study (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…PVL-negative CA-MRSA included ST8 strain NN50 (18), ST88 strain NN51 (39), ST89 strain NN7 (39), and ST91 strain NN15 (39); ST88, ST89, and ST91 strains were from bullous impetigo and were exfoliative toxin (ET)-positive. The New York/Japan ST5/SCCmecII clone (a major HA-MRSA clone in Japan), used in this study, included reference strains Mu50 and N315 and clinical strains I6 and I8 (34). PVL-positive ST8 CA-MRSA USA300 included the type strain (USA300-0114) and strains NN36 and NN47 isolated in Japan (13).…”
Section: Distribution Of Pvl-positive St30 Mrsa In Japanmentioning
confidence: 99%
“…CA-MRSA (34,37,38). In this study, we investigated PVL-positive ST30 MRSA since the 1980s in Japan focusing on its evolution and virulence.…”
mentioning
confidence: 99%
“…Moreover, two lukS/F-PVpositive MRSA strains were isolated in 2003 and 2004 from Japanese hospitals (Takizawa et al 2005), emphasizing the necessity to monitor lukS/F-PV-positive MRSA clones for preventing the spread of infection. SCCmec typing is useful for characterizing CA-MRSA clones.…”
mentioning
confidence: 99%